2021
DOI: 10.3390/jof7040295
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification and Analysis of Nilaparvata lugens microRNAs during Challenge with the Entomopathogenic Fungus Metarhizium anisopliae

Abstract: The resistance of the notorious rice pest Nilaparvata lugens to many insecticides has caused significant concerns. Our previous study demonstrated that the fungus Metarhizium anisopliae CQMa421 shows great potential for the control of this pest, but the interactions between them are still unclear. Thus, we further investigated fungal infection-related microRNAs (miRNAs) in N. lugens during M. anisopliae CQMa421 challenge using Illumina sequencing. In this study, we constructed twenty-four small RNA libraries o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…While bacterial endosymbionts affect miRNA profiles in planthoppers, entomopathogenic microbes were also found to cause specific changes in miRNA profiles. In their investigation of the impact of the entomopathogenic fungus Metarhizium anisopliae against BPH ( N. lugens ), Xie et al (2021) found that the high biocontrol potential of M. anisopliae was linked to specific changes in miRNA profiles, and target gene functions were predicted to include genes involved in energy metabolism, ubiquitin-mediated proteolysis, and mitogen-activated protein kinase signaling pathway. A previous study investigated the transcriptome of M. anisopliae- challenged insects and indicated that fungal infection caused specific changes in the expression of membrane-related genes and genes related to cellular immune response and humoral immune factors ( Zhang et al, 2015 ).…”
Section: Roles Of Microbiota and Srnas In Planthoppersmentioning
confidence: 99%
“…While bacterial endosymbionts affect miRNA profiles in planthoppers, entomopathogenic microbes were also found to cause specific changes in miRNA profiles. In their investigation of the impact of the entomopathogenic fungus Metarhizium anisopliae against BPH ( N. lugens ), Xie et al (2021) found that the high biocontrol potential of M. anisopliae was linked to specific changes in miRNA profiles, and target gene functions were predicted to include genes involved in energy metabolism, ubiquitin-mediated proteolysis, and mitogen-activated protein kinase signaling pathway. A previous study investigated the transcriptome of M. anisopliae- challenged insects and indicated that fungal infection caused specific changes in the expression of membrane-related genes and genes related to cellular immune response and humoral immune factors ( Zhang et al, 2015 ).…”
Section: Roles Of Microbiota and Srnas In Planthoppersmentioning
confidence: 99%
“…Meanwhile, the energy metabolism of the host is intensive, and many antimicrobial peptides are generated to function on the pathogens [ 24 ]. Although a few studies have examined the interaction between insect hosts and pathogens under different conditions by transcriptomic profiling [ 25 , 26 , 27 ], the means by which the rice planthopper S. furcifera responds to fungal infection is less known, especially in terms of their behaviors.…”
Section: Introductionmentioning
confidence: 99%